The effects of iloprost and beta3 receptor agonist on TRPA1 and TRPC1 immunreactivity in an experimental lower extremty ischemia-reperfusion injury model - Ustunel, Latif; Ozguler, Ibrahim Murat (Tubitak Scientific & Technological Research Council Turkey, 2021)
Background/aim: In this study, we aimed to investigate the effects of antioxidant iloprost (ILO) and ss 3 adrenergic receptor agonist (BRL) on transient receptor potential ankyrin 1 (TRPA1) and transient receptor potential canonical 1 (TRPC1) ion channels on an experimental ischemia and reperfusion injury model in 30 male Wistar albino rats aged 8-10 weeks. Materials and methods: Wistar Albino rats aged were divided into 5 equal groups. Group I Sham operation, Group II IR (ischemia-reperfusion) procedure, Group III IR + intravenous ILO administration, Group IV IR + intraperitoneal BRL administration, and Group V IR + intravenous ILO + intraperitoneal BRL administration group. Two ng/kg/min ILO intravenous infusion was applied to the ILO group. A single dose of 5 mcg/kg BRL intraperitoneal was applied to BRL group. TOS (total oxidant status), TRPA1, and TRPC1 levels were measured with ELISA (enzyme linked immunosorbent assay) in serum, immunohistochemical staining in musculus quadriceps femoris tissue. Results: Compared with the sham group, the IR group had a statistically significant increase in serum levels of TOS (p = 0.004), TRPA1 (p = 0.002), and TRPC1 (p = 0.008) along with TRPA1-and TRPC1-immunoreactivity (p = 0.005, each) in the tissue. When compared with the IR group in terms of serum levels of TRPA1 and tissue TRPA1-immunoreactivity, although there was no statistically significant difference in the IR+Ilo (p = 0.257 and p = 0.429, respectively), IR+Brl (p = 0.024 and p = 0.177, respectively), and IR+Ilo+Brl (p = 0.024 and p = 0.329, respectively) groups, serum levels of TOS and TRPC1 along with tissue TRPC1-immunoreactivity were statistically significantly reduced in the IR+Ilo (p = 0.002, p = 0.008, and p = 0.004, respectively), IR+Brl (p = 0.004, p = 0.008, and p = 0.004, respectively), and IR+Ilo+Brl groups (p = 0.002, p = 0.008, and p = 0.004, respectively). Conclusion: In IR group serum TOS, TRPA1 and TRPC1 levels ,and tissue TRPA1 and TRPC1 immunoreactivity were statistically significant increase when compared to the sham group. In IR+ILO, IR+BRL and IR+ILO+BRL groups serum TRPA1 and tissue TRPA1 immunoreactivity did not change when compared to IR group. Serum TOS and TRPC1 levels, tissue TRPC1 immunoreactivty were statistically significant decreased when compared to IR group. More detailed and expanded population studies are needed to discuss our results.
Keywords: Rat; iloprost; BRL; TRP; ischemia; reperfusion